TNF-α and IL-8 in Acute Stroke and the Modulation of these Cytokines by Antiplatelet Agents - Al-Bahrani, Ali; Taha, Safa; Shaath, Husain; Bakhiet, Moiz (Current Neurovascular Research, 2007)
Stroke is associated with elevation of several proinflammatory cytokines such as tumor necrosis factor alpha (TNF-α) and interleukin (IL)-8 that are correlated with central nervous system (CNS) injury. Anti-platelet therapies are important agents in stroke management. The role of antiplatelets as anti-inflammatory agents is not known in acute stroke patients. Furthermore, their effect on induction of potential cytokines as TNF-α and IL-8 in those patients is still not clear. Thus, we herein examined the induction of TNF-α and IL-8 in acute stroke patients and examined the effects of the antiplatelets drugs aspirin, clopidogrel and dipyridamole, and piracetam in their induction. Cytokines were detected intracellularly in leukocytes from patients who had first acute ischemic stroke and from matched controls by immunocytochemistry. The results showed significant increase of spontaneously produced TNF-α and IL-8 in patients compared to control. This induction was significantly inhibited differently by each drug and dual drug agents. The data of this work suggest that antiplatelets agents may have a role in inhibition of stroke mediated proinflammatory cytokine effects, which may initiate a new aspect of the role of antiplatelets in the treatment of acute ischemic stroke.
Keywords: Brain